2020
DOI: 10.1038/s41598-020-60777-x
|View full text |Cite|
|
Sign up to set email alerts
|

A soluble truncated tau species related to cognitive dysfunction is elevated in the brain of cognitively impaired human individuals

Abstract: Neurofibrillary tangles are a pathological hallmark of Alzheimer's disease, and their levels correlate with the severity of cognitive dysfunction in humans. However, experimental evidence suggests that soluble tau species cause cognitive deficits and memory impairment. Our recent study suggests that caspase-2 (Casp2)-catalyzed tau cleavage at aspartate 314 mediates synaptic dysfunction and memory impairment in mouse and cellular models of neurodegenerative disorders. Δtau314, the C-terminallytruncated cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…Intriguingly, recent reports suggest that, indeed, caspase-2-dependent generation of Δtau314 is also responsible for the cognitive deficits seen in Lewy body disease, non-dementia Parkinson's disease as well as Huntington's disease [88,89]. Strikingly, a recent study on human individuals suffering from AD found that the levels of Δtau314 correlate with cognitive impairment, and also caspase-2 protein levels were increased in these patients, confirming the findings made in mouse models [90]. In addition to cleavage of tau, caspase-2 was found to shape dendritic spines by regulating AMPA receptor internalization via proteolytic cleavage of Rictor, thus inhibiting mTORC2 signaling.…”
Section: Caspase-2 and The Piddosome In Neuronal Development And Disesupporting
confidence: 69%
“…Intriguingly, recent reports suggest that, indeed, caspase-2-dependent generation of Δtau314 is also responsible for the cognitive deficits seen in Lewy body disease, non-dementia Parkinson's disease as well as Huntington's disease [88,89]. Strikingly, a recent study on human individuals suffering from AD found that the levels of Δtau314 correlate with cognitive impairment, and also caspase-2 protein levels were increased in these patients, confirming the findings made in mouse models [90]. In addition to cleavage of tau, caspase-2 was found to shape dendritic spines by regulating AMPA receptor internalization via proteolytic cleavage of Rictor, thus inhibiting mTORC2 signaling.…”
Section: Caspase-2 and The Piddosome In Neuronal Development And Disesupporting
confidence: 69%
“…This C-terminally truncated fragment of tau mis-localizes to dendritic spines and causes cognitive dysfunction in an animal model of tauopathy (51). A recent report indicates elevated levels of this fragment in cognitively impaired human kindreds (78). A 35 kDa N-terminally truncated tau fragment entailing the microtubule-binding repeat domains was reported to be present in post-mortem brains of patients diagnosed with tauopathies in which 4R isoforms predominate (79).…”
Section: Proteolysismentioning
confidence: 97%
“…Interestingly, tau and α-syn also seem to contribute to HD pathology (Tomás-Zapico et al 2012, Fernández-Nogales et al 2014). Specific tau modifications and cleavage products associated with cognitive decline in AD were found in the brains of HD patients and suggested HD as a new tauopathy (Liu et al 2020, Fernández-Nogales et al 2014). Similarly, increased levels of α-syn were observed in plasma of patients with HD (Shalash et al 2017, Breza et al 2020).…”
Section: Introductionmentioning
confidence: 98%